Factors that influence the occurrence of perineal laceration in birth (Research, Society and Development, 2022)
The aim of this study was to analyze the factors that influence the occurrence of perineal laceration in childbirth. This is an integrative literature review carried out by searching the LILACS, BDENF and MEDLINE databases by crossing the descriptors Normal childbirth AND Perineum, Normal childbirth AND Laceration, Trauma AND Perineum, covering the period from 2016 to 2021. The results showed that the factors that influenced the occurrence of perineal laceration were maternal age, nulliparity, gestational age ≥ 42 weeks, fetal head circumference > 35 cm, 2nd stage of labor > 02 (two) hours, operative vaginal delivery, use of oxytocin and induction of labor. Therefore, it was possible to conclude that the highest proportions of these factors were related to maternal characteristics and interventions performed during labor, making it necessary to develop prophylactic strategies in order to reduce the rates of lacerations in the services.